Improving Supply Chain Management Traceability Using Blockchain Technology Through Hyperledger Composer - Mahira Imron, Faqih; Okdinawati, Liane (Fakultas Ekonomi Universitas Gresik, 2023)
The management of supply chain (SCM) is of paramount importance in guaranteeing the effective and dependable transportation of commodities. Notwithstanding, impediments such as erroneous data and data tampering present noteworthy hindrance to attaining traceability and transparency in the supply chain management (SCM) process at Angkasa Pura Logistic (APLog). The objective of this investigation is to tackle the aforementioned concerns by examining the capabilities of blockchain technology, with a particular focus on the implementation of Hyperledger Composer. The author employed focus group discussions to obtain current operational data as well as data spanning a period of three years in order to analyze the percentage of factors contributing to issues. Through the utilization of Hyperledger and smart contracts, an author has the ability to provide recommendations and propose novel concepts for the application of this technology in their respective solutions